Accountants and Society : Serving the Public Interest - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed how accountants can best serve the public interest. Over the last 15 years, the Bank have seen freedom blossom and with it an expanded role for civil society. Today five billion people live in a market system - up from 1 billion a decade ago. Lack of institutional capacity, poor governance, and public sector management remain major impediments to growth and development. The Bank is holding anti-corruption seminars and workshops for parliamentarians and journalists; making sure that our own processes meet the highest standards of transparency and propriety; and pushing ahead with deregulation, institutional, and policy reform. The Bank can and is working to improve accounting and auditing capacity building, in Ghana, Zambia, China, Pakistan, and Indonesia among others.